Model standards of conduct for mediators - (:unkn) unknown (My University, 2016)
The Model Standards of Conduct for Mediators was prepared in 1994 by theAmerican Arbitration Association, the American Bar Association’s Section of DisputeResolution, and the Association for Conflict Resolution. A joint committee consisting ofrepresentatives from the same successor organizations revised the Model Standards in2005. Both the original 1994 version and the 2005 revision have been approved by eachparticipating organization.